Danning tablets might improve glucose and lipid metabolism in asymptomatic T2MD patients after cholecystectomy: A cohort study. Issue 50 (17th December 2021) - Chen, Weijie; Zhou, Shengnan; Xiao, Jianchun; Liu, Wei; Qu, Qiang; He, Xiaodong
Abstract : Abstract: Considering the role of bile acids in glucose metabolism and the effect of farnesoid X receptor agonists on bile acids, we investigated the possible effect of Danning tablets (DNTs), a type of farnesoid X receptor agonist, on glucose and lipid metabolism in asymptomatic type 2 diabetes mellitus (T2DM) patients. A series of asymptomatic T2DM patients who underwent cholecystectomy at least 2 years prior and were regularly followed up in our hospital were included in our analysis. According to their choice, they were divided into 2 groups: the DNT group and the control group. Demographic data, body weight, food intake, effects on diabetes control, and biomedical variables were collected. After propensity score matching, a total of 64 T2DM patients (41 males and 23 females) were included in the analysis. The amount of daily food intake (kcals) and diet composition were little changed 6-months after DNT administration ( P = .612). However, the average fasting glucose level of the DNT group decreased from 9.5 ± 1.4 mmol/L to 8.3 ± 1.6 mmol/L ( P < .001), and the level of hemoglobin A1c decreased from 8.3 ± 1.1% to 7.6 ± 1.0% ( P = .001). The total cholesterol level ( P = .024) and low-density lipoprotein cholesterol level ( P = .034) decreased significantly ( P = .018). Moreover, the average level of total bile acids decreased from 6.05 ± 2.60 μmol/L to 5.10 ± 1.83 μmol/L in the DNT group ( P = .037), and the level of glucagon-like peptide-1 significantly increased from 6.93 ± 4.94 pmol/L to 11.25 ± 5.88 pmol/L ( P < .001). The results of our study show that DNT intake improved glucose and lipid metabolism and increased the level of glucagon-like peptide-1. Trial registration: registered in Chinese Clinical Trial Registry (No. ChiCTR1900027823).